2016
DOI: 10.1590/1518-8345.1316.2800
|View full text |Cite
|
Sign up to set email alerts
|

Drug-drug interactions and adverse drug reactions in polypharmacy among older adults: an integrative review

Abstract: Objective: to identify and summarize studies examining both drug-drug interactions (DDI) and adverse drug reactions (ADR) in older adults polymedicated. Methods: an integrative review of studies published from January 2008 to December 2013, according to inclusion and exclusion criteria, in MEDLINE and EMBASE electronic databases were performed. Results: forty-seven full-text studies including 14,624,492 older adults (≥ 60 years) were analyzed: 24 (51.1%) concerning ADR, 14 (29.8%) DDI, and 9 studies (19.1%) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 52 publications
(106 reference statements)
1
89
0
15
Order By: Relevance
“…Polypharmacy increases the risk of a wide range of undesirable health outcomes and events such as adverse drug events and drug-drug interactions [4,5]. Polypharmacy is associated with reduced medication adherence [6][7][8][9] and an increase in potentially inappropriate medication (PIM) use [10].…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy increases the risk of a wide range of undesirable health outcomes and events such as adverse drug events and drug-drug interactions [4,5]. Polypharmacy is associated with reduced medication adherence [6][7][8][9] and an increase in potentially inappropriate medication (PIM) use [10].…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy is said to not only increase irrational use of drugs but also can increase the risk of drug interactions, medication errors and adverse effects. 11,12 In present study it was observed that the percentage of drugs prescribed by generic name was 41.4%. Use of generic drugs is said to decrease the expenditure of medicine.…”
Section: Discussionmentioning
confidence: 48%
“…42,43 Frailty is also associated with a deterioration in physical function and increased risk of falls, injury, fracture, hospital admission and mortality. 39,[44][45][46][47][48][49] Although the use of anticholinergic and sedative medications further impairs physical function, 16 there were no significant differences between drug burden and the frail and non-frail groups, possibly due to the sample size and self-reported measures of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…The older people residing in ACFs portray vulnerability and their health needs are complex due to multiple comorbidities and age‐related changes in pharmacokinetic and pharmacodynamic characteristics . Frailty is also associated with a deterioration in physical function and increased risk of falls, injury, fracture, hospital admission and mortality . Although the use of anticholinergic and sedative medications further impairs physical function, there were no significant differences between drug burden and the frail and non‐frail groups, possibly due to the sample size and self‐reported measures of frailty.…”
Section: Discussionmentioning
confidence: 99%